HPV infection among rural American Indian women and urban white women in South Dakota: an HPV prevalence study - Muller Clemma J (BMC Infectious Diseases, 2011)
Abstract Background High-risk strains of human papillomavirus (HPV) cause cervical cancer. American Indian (AI) women in the Northern Plains of the U.S. have significantly higher incidence and mortality rates for cervical cancer than White women in the same geographical area. We compared HPV prevalence, patterns of HPV types, and infection with multiple HPV types in AI and White women living in South Dakota, U.S. Methods We analyzed the HPV status of cervical samples collected in 2006-2008 from women aged 18-65 years who attended two rural AI reservation clinics (n = 235) or an urban clinic in the same area serving mostly White women (n = 246). Data collection occurred before HPV vaccination was available to study participants. HPV DNA was amplified by using the L1 consensus primer system and an HPV Linear Array detection assay to identify HPV types. We used chi-square tests to compare HPV variables, with percentages standardized by age and lifetime number of sexual partners. Results Compared to White women, AI women were younger (p = 0.01) and reported more sexual partners (p < 0.001). A lower percentage of AI women tested negative for HPV infection compared to Whites (58% [95% CI = 51-65] vs. 77% [95% CI = 71-82]; p < 0.001), and a higher percentage of AI women were infected by oncogenic types (30% [95% CI = 25-36] vs. 16% [95% CI = 11-21]; p = 0.001). Infections among AI women showed a wider variety and very different pattern of HPV types, including a higher prevalence of mixed HPV infections (19% [95% CI = 26-38] vs. 7% [95% CI = 4-11]; p = 0.001). AI women had a higher percentage of HPV infections that were not preventable by HPV vaccination (32% [95% CI = 26-38] vs. 15% [95% CI = 11-21]; p < 0.001). Conclusions A higher HPV burden and a different HPV genotyping profile may contribute to the high rate of cervical cancer among AI women.